Risk behaviors for eating disorders and depressive symptoms: a study of female adolescents in Juiz de Fora, Minas Gerais State, Brazil - Leonardo de Sousa Fortes; Juliana Fernandes Filgueiras; Maria Elisa Caputo Ferreira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
The objective of this study was to analyze the relationship between depressive symptoms and eating disorders in female adolescents. The sample included 371 girls ranging from 12 to 16 years of age in Juiz de Fora, Minas Gerais State, Brazil. The study used the Eating Attitudes Test (EAT-26) and Major Depression Inventory (MDI) to evaluate eating disorders and depressive symptoms, respectively. The linear regression model showed that 18% of the EAT-26 scores were influenced by MDI (F(1, 370) = 14.18; p = 0.001). Moreover, the findings indicated a statistically significant association between depressive symptoms and eating disorders (χ2 = 14.71; Wald = 12.90; p = 0.001). The authors concluded that depressive symptoms were related to eating disorders in female adolescents. Thus, girls with some level of depression showed a greater tendency to adopt disordered eating as a daily habit.